Optimasi Keamanan Jaringan Menggunakan Extended ACL pada Infrastruktur VLAN - Janeman Sumah; Robert Manaha; wendel herman selsily; Trientje Marlein Tamtelahitu; Marthevienty H.T. Soumokil (Yayasan Literasi Sains Indonesia, 2026)
Successful network scalability and management may not be immediately applicable to larger scales. As the network becomes more complex, VLAN and ACL management and administration can become a greater challenge, especially in terms of maintenance and troubleshooting. This study simulates the implementation of a VLAN network for the Faculty of Computer Science UKIM using a multilayer switch and Cisco Packet Tracer software. The network includes 3 IP servers and 4 VLANs. The configured servers include the Faculty server (192.168.10.10/24), Lab1 server (192.168.20.10/24), and Lab2 server (192.168.30.10/24), while the VLANs consist of MHS_FILKOM (ID 100), DOSEN_FILKOM (ID 200), PEGAWAI_FILKOM (ID 300), and ADMIN_FILKOM (ID 400). An extended ACL configuration is applied to regulate access on this network. The test results showed that HTTP access to the Faculty server was successfully blocked, thus protecting the server from unauthorized access via port 80. In addition, SSH access from the Admin network to all servers worked properly, allowing for secure server management. Communication between Lab1 and Lab2 servers was restricted to ICMP (ping) only, while other traffic was successfully blocked to maintain security between the servers. Internal traffic between VLANs and servers ran smoothly, ensuring smooth communication between the networks. Access to the Faculty server was also restricted to the Admin network (192.168.40.0/24), providing strict access control and improving overall network security. This configuration provides better security and allows for more effective network management.